2014
DOI: 10.1007/s10531-014-0645-2
|View full text |Cite
|
Sign up to set email alerts
|

Improved appreciation of the functioning and importance of biological soil crusts in Europe: the Soil Crust International Project (SCIN)

Abstract: Here we report details of the European research initiative “Soil Crust International” (SCIN) focusing on the biodiversity of biological soil crusts (BSC, composed of bacteria, algae, lichens, and bryophytes) and on functional aspects in their specific environment. Known as the so-called “colored soil lichen community” (Bunte Erdflechtengesellschaft), these BSCs occur all over Europe, extending into subtropical and arid regions. Our goal is to study the uniqueness of these BSCs on the regional scale and investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
94
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 97 publications
(99 citation statements)
references
References 42 publications
5
94
0
Order By: Relevance
“…Green algae are rarely the dominant crustforming organisms and they occur in low abundance or may be present as dormant resting stages, which are hard to detect. This is supported by other studies that detected, at least from Hochtor, Austria, only a minor proportion of green algae (Büdel et al, 2014;Peer et al, 2013). 20…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…Green algae are rarely the dominant crustforming organisms and they occur in low abundance or may be present as dormant resting stages, which are hard to detect. This is supported by other studies that detected, at least from Hochtor, Austria, only a minor proportion of green algae (Büdel et al, 2014;Peer et al, 2013). 20…”
Section: Discussionsupporting
confidence: 75%
“…This becomes even more interesting when other findings are considered, where Büdel et al, (2014) showed that within the microbiome of BSC from Hochtor, cyanobacteria contributed only 1.6 % to the total bacterial diversity, whereas we show here that they occupy 20 % of space within the crust.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…Possibly the main advantage would be the acceleration in the succession procedure, a process that normally happens very slowly in case of natural systems (Mor-Mussery et al 2015). In addition, new restoration systems make the ability to design a real BSC for any required special restoration conditions possible (Büdel et al 2014).…”
Section: Conventional Systems Of Bsc Restorationmentioning
confidence: 99%